A nonanalog Pliocene ungulate community at Laetoli with implications for the paleoecology of Australopithecus afarensis. Issue 167 (June 2022) - Fillion, Elizabeth N.; Harrison, Terry; Kwekason, Amandus
Abstract: The dietary guild structure of ungulate communities is a useful paleoecological tool for understanding the context of hominin paleobiology and evolution. Ungulates are well represented in the fossil record, and their dietary preferences reflect those of major habitat types. However, paleoecology relies on modern ecological patterns as analogs for recreating ecologies of the past. It has previously been suggested that for much of the Pliocene, no such modern analogs exist for the herbivore communities associated with hominins in eastern Africa. This study aims to determine whether the ungulate community associated with A. afarensis at the Pliocene site of Laetoli, Tanzania, shares similarities with extant communities or whether it lacks a modern analog. Our multiproxy approach using mesowear, hypsodonty, and stable carbon isotopes of tooth enamel to infer the diets of ungulates in the Upper Laetolil Beds shows that this community is dominated by browsers and mixed feeders and has a very low prevalence of grazers and frugivores. This dietary guild composition distinguishes the Upper Laetolil Beds from modern African communities and suggests either that the Upper Laetolil Beds had a unique vegetation structure which was able to support a higher diversity of browsing ungulates than that exists in African ecosystems today or that it retained an ungulate community that was resilient to environmental change. The Upper Laetolil Beds ungulate community is also unique relative to other mid-Pliocene communities in eastern Africa, some of which are similar to extant communities, while others, such as Laetoli, lack modern counterparts. This suggests that A. afarensis was a eurytopic species that inhabited a variety of ecosystems, including those with and without modern analogs. The co-occurrence of both analog and nonanalog communities in the Pliocene suggests that the transformation toward ungulate communities of modern aspect occurred asynchronously in eastern Africa. Highlights: We use multiple proxies to infer diets of ungulates in the Upper Laetolil Beds. The community is dominated by browsing and mixed-feeding species. This sets it apart from modern African ungulate communities. Both analog and nonanalog communities occur in the Pliocene of eastern Africa. This has implications for the paleobiology of Australopithecus afarensis.